TANGGUNG JAWAB PENGURUS TERHADAP PELANGGARAN PRINSIP-PRINSIP KOPERASI - Ni Nyoman Adi Astiti (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Cooperatives are based on principles of kinship is one form of business entity that plays a role in the development of Indonesia's economy. Cooperative essentially contains two objectives , namely economic goals and social goals. Cooperative is a system and we know this system is a set of components or parts that are interrelated together serve achieve goals. The values on which the cooperative is independence, responsible, democracy, equality, justice, and solidarity . Ethical values are believed to be members is honesty, keterbukaan, social responsibility, and concern for others. Operative principle is an integral and inseparable in the life of cooperatives. By implementing the overall principles of the cooperative manifesting itself as a business entity as well as people's economic movement of social character. The cooperative principle is the basic essence of cooperative work as a business entity and it is typical and cooperative identity that sets it apart from other business entities. The responsibility of the board of the co-operative principles are still not implemented optimally. There are still many cooperatives that violate cooperative principles. The legal consequences of the violation of the principles of the cooperative form of dissolution actions undertaken by the government.